2021
DOI: 10.1371/journal.pone.0249214
|View full text |Cite
|
Sign up to set email alerts
|

Maternal health care services utilization amidstCOVID-19 pandemic in West Shoa zone, central Ethiopia

Abstract: The novel coronavirus (COVID-19) is an infectious disease caused by a newly discovered coronavirus. Despite strong efforts that have been taking place to control the pandemic globally, the virus is on the rise in many countries. Hence, this study assessed the maternal health care services utilization amidst the COVID-19 pandemic in West Shoa zone, Central Ethiopia. A community-based cross-sectional study was conducted among 844 pregnant women or those who gave birth in the last 6 months before the study. A mul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
78
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(86 citation statements)
references
References 18 publications
7
78
1
Order By: Relevance
“…The impacts of such public health measures must also be considered as to how they impact within different socioeconomic contexts, as changes to service use during the pandemic have not been universal, impacting more on those in lower socioeconomic circumstances. 43 While the number of ANC visits decreased, our delivery rate did not decline by the same amount. Kawempe hospital caters for a population of 2 million people, yet the number of women attending four ANC visits remains below 90%, although the majority of women in Kampala still deliver in hospital (94%).…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…The impacts of such public health measures must also be considered as to how they impact within different socioeconomic contexts, as changes to service use during the pandemic have not been universal, impacting more on those in lower socioeconomic circumstances. 43 While the number of ANC visits decreased, our delivery rate did not decline by the same amount. Kawempe hospital caters for a population of 2 million people, yet the number of women attending four ANC visits remains below 90%, although the majority of women in Kampala still deliver in hospital (94%).…”
Section: Discussionmentioning
confidence: 67%
“…The impacts of such public health measures must also be considered as to how they impact within different socioeconomic contexts, as changes to service use during the pandemic have not been universal, impacting more on those in lower socioeconomic circumstances. 43 …”
Section: Discussionmentioning
confidence: 99%
“…This restriction affected access to elective antenatal visits [ 13 ]. The level of maternal education, distance from maternal health clinics, and monthly income were directly related to the reduced utilisation of maternal healthcare clinics during the COVID-19 pandemic [ 14 ].…”
Section: Antenatal Care Challenges and Role Of Telemedicinementioning
confidence: 99%
“…Several studies from different countries around the world showed the negative impacts of COVID-19 pandemic on MCH services [17][18][19][20][21]. In Ethiopia, some studies from various regions showed reductions in MCH services during the early period of the COVID-19 pandemic [6,11,[22][23][24]. However, trends in the MCH care services performance during and after national lockdown have not been adequately assessed, particularly in Addis Ababa, the capital city where most COVID-19 cases were detected.…”
Section: Introductionmentioning
confidence: 99%